Spiritual domain in human civlization - Ab. Razak, Ratna Roshida; Mohd Yusoff, Ahmad Nasir (Faculty of Agriculture and Food Sciences, Universiti Putra Malaysia Bintulu Sarawak Campus, 2019)
Spirituality is a powerful dimension of human experience. As written in the Bahai text, "No matter how far the material world advances, it cannot establish the happiness of mankind. Only when material and spiritual civilization are linked and coordinated will happiness be assured, for in material civilization good and evil advance together and maintain the same pace" Material civilization should be integrated with spiritual civilization, like a lamp that needs a light to give the lamp a meaning, purpose and value. If the material and spiritual civilization become united, then we will have the light and the lamp together, and the outcome will be perfect. For material civilization is like unto a beautiful body, and spiritual civilization is like unto the spirit of life. If that phenomenal spirit of life enters this beautiful body, the body will become a channel for the distribution and development of the perfections of humanity. This paper aims to address the importance in enhancing spirituality in our human family by trying to give answers to these two key questions, firstly the origins of the deficiencies of the current civilization and secondly, how can humanity build up civilization based on the spiritual treasuries, which comprises of meaning, purpose and value of life, existing in all cultures, religions and traditions.